Lost letters from Vienna - Course, Sue, 1933- (Wild Dingo Press, 2019)
A unique and fascinating memoir of a wealthy Viennese family whose fate was brutally disrupted with the Nazi occupation. In 2000, former nurse, environmental activist and grandmother, Sue Course, discovers a suitcase from her mother's house crammed with letters from her large Jewish family, dating back to 1938. Born in 1933, Sue and her parents were the first of her family to flee Vienna in 1938, emigrating to Melbourne. Despite the chaos of war and occupation, postal services across the globe kept the letters coming; letters connecting the many aunts, uncles, cousins and grandparents. They reveal incredible journeys of struggle, survival and adaptation, travail and lost opportunities, as they lose all control over their futures.